Three studies of the associations of cognitive ability, health, and wealth among the elderly - Fernatt, Frederick Ray (Kansas State University, 2016)
This dissertation consists of three studies exploring the relationship between cognitive abilities, health, and wealth related variables among the elderly. For all three studies, the life cycle hypotheses provided the basis of the theoretical framework and utilized data from the 2000 through 2010 panels of the Health and Retirement Study (HRS). The first study compared the cognitive abilities of non-married households with the cognitive abilities of married households in order to examine the effect of marital status on household wealth. The second study examines the relationship of two aspects of cognitive ability (fluid intelligence and crystallized intelligence) and wealth for couples married to the same spouse for all HRS panels for 2000 to 2010. The third study examines the relationship of cognitive ability, emotional health, physical health, and wealth for couples married to the same spouse for all HRS panels for 2000 to 2010. Results identified significant associations among marital status, cognitive abilities, and health with wealth. These findings contribute to the field of financial planning by providing useful information about how marital status, cognitive functioning, and health affect the household wealth of the elderly. Financial service practitioners, regulators, researchers, and caregivers can apply these findings to develop approaches to assist the elderly manage their household wealth.
Keywords: Cognition; Memory; Elderly